2013
DOI: 10.1021/es400329t
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bisphenol S Exposure on Endocrine Functions and Reproduction of Zebrafish

Abstract: While bisphenol S (BPS) has been frequently detected both in environment and biota, limited information is available on their effects of endocrine system. In the present study, adult zebrafish pairs were exposed to 0.5, 5, and 50 μg/L of BPS for 21 d, and the effects on reproduction, sex steroid hormones, and transcription of the genes belonging to the hypothalamic-pituitary-gonad (HPG) axis were investigated. The adverse effects on performances of F1 generation were further examined with or without subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
152
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(165 citation statements)
references
References 35 publications
13
152
0
Order By: Relevance
“…They found that both chemicals behaved like oestrogens, but were 100,000-fold less active than oestradiol 3 . Choi and his colleagues discovered that zebrafish exposed to 0.5 micrograms of BPS per litre of water -about one-sixth of the maximum concentration detected in the environment -had fewer eggs, more malformed offspring and higher oestrogen to testosterone ratios than untreated zebrafish 4 . "High concentrations of BPS have the same effect as high concentrations of BPA, " says Habert, who has conducted preliminary experiments on the effect of BPS on mouse and human fetal testis cells.…”
Section: A Key To Actionmentioning
confidence: 99%
“…They found that both chemicals behaved like oestrogens, but were 100,000-fold less active than oestradiol 3 . Choi and his colleagues discovered that zebrafish exposed to 0.5 micrograms of BPS per litre of water -about one-sixth of the maximum concentration detected in the environment -had fewer eggs, more malformed offspring and higher oestrogen to testosterone ratios than untreated zebrafish 4 . "High concentrations of BPS have the same effect as high concentrations of BPA, " says Habert, who has conducted preliminary experiments on the effect of BPS on mouse and human fetal testis cells.…”
Section: A Key To Actionmentioning
confidence: 99%
“…Many endocrine disruptors are known to modulate sex steroid signaling and the HPG axis (Ankley et al, 2009;Ji et al, 2013); thus, it is possible that exposure to MTA may also affect plasma sex hormone levels. In our study, the E2 and T levels in female fish plasma and the 11-KT level in male fish plasma were significantly decreased after MTA exposure for 21 days, further demonstrating that synthetic progestins can adversely affect fish of both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Many endocrine disruptors are known to modulate sex steroid signaling and the hypothalamic-pituitary-gonadal (HPG) axis (Villeneuve et al, 2007;Ankley et al, 2009;Ji et al, 2013) by interfering with endocrine functions and affecting both development and reproduction. Thus, we also measured the concentrations of sex hormones in zebrafish and examined the effect of MTA on the transcription of key genes along the HPG axis, with the intention of identifying potential target genes and the potential mode of action of MTA.…”
Section: Introductionmentioning
confidence: 99%
“…the higher circulating concentrations of estradiol in female zebrafish(Deng et al, 2010; Liu et al, 2012;Ma et al, 2012;Ji et al, 2013; Liu et al, 2013; Lu et al, 2014;Yu et al, 2014; …”
mentioning
confidence: 99%